Identifikasi Kandungan Bakteri Vibrio cholerae pada Produk Olahan Pepes Ikan Tuna (Thunnus sp.): Identification of the Bacterial Content of Vibrio cholerae On Tuna Fish Pepes (Thunnus sp.) - Kiki Haetami; Inas Maya Tamimah Hanun (PharmaCine : Journal of Pharmacy, Medical and Health Science, 2024)
Tuna (Thunnus sp.) is one of the potential fishery products because it has a high protein content. Tuna fish can be processed into various kinds of processing, one of which is pepes ikan which is a traditional Indonesia dish. Processed fishery products such as pepes can also experience a decrease in quality, one of which can be caused by the presence of bacteria, such as Vibrio cholerae bacteria. Vibrio cholerae is an opportunistic pathogen in estuarine and marine environments. These bacteria can be transferred into the food matrix causing illness if consumed by humans. The purpose of this study is to identify the content of Vibrio cholerae bacteria in tuna fish pepes processed products. The results of biochemical tests based on SNI 01-2332.4-2006 show that tuna fish pepes originating from one MSME in the Special Region of Yogyakarta does not contain or are negative for Vibrio cholerae so that it is suitable for marketing and human consumption. Keywords: Microbiology, Fishery Products, Processed Products, Tuna Fish, Vibrio cholerae.